2015
DOI: 10.1016/j.fob.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antibiotic exposure on eicosanoid generation from arachidonic acid and gene expression in a primitive chordate,Branchiostoma belcheri

Abstract: HighlightsChloramphenicol treatment induced immunosuppression and severe tissue damage in amphioxus.KEGG clustering showed that chloramphenicol and ampicillin treatment resulted in immunostimulation.Chloramphenicol treatment induced a ∼3-fold decrease of eicosanoid levels.Chloramphenicol and ampicillin treatment resulted in a 1.7-fold increase of eicosanoid levels.Eicosanoids derived from arachidonic acid provide insights into the effect of chloramphenicol treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A multitude of ARA studies revealed decreased EPA deposition in fish in response to increasing dietary ARA levels. 17,20,22,73,[82][83][84]86,92,[94][95][96][97][98]104,105,[108][109][110][111][112][113][114]116,121,125,135,136,139,140,151,163,172,176,209,210 Therefore, no doubts should be present that increased dietary ARA displaces EPA retention in fish tissues.…”
Section: Interaction Between Ara and Other Lc-pufamentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of ARA studies revealed decreased EPA deposition in fish in response to increasing dietary ARA levels. 17,20,22,73,[82][83][84]86,92,[94][95][96][97][98]104,105,[108][109][110][111][112][113][114]116,121,125,135,136,139,140,151,163,172,176,209,210 Therefore, no doubts should be present that increased dietary ARA displaces EPA retention in fish tissues.…”
Section: Interaction Between Ara and Other Lc-pufamentioning
confidence: 99%
“…First, a direct competition between ARA and EPA is present when they are incorporated into fish tissues, especially when incorporated into phospholipids and cellular membranes. A multitude of ARA studies revealed decreased EPA deposition in fish in response to increasing dietary ARA levels 17,20,22,73,82–84,86,92,94–98,104,105,108–114,116,121,125,135,136,139,140,151,163,172,176,209,210 . Therefore, no doubts should be present that increased dietary ARA displaces EPA retention in fish tissues.…”
Section: Interaction Between Ara and Other Nutrients And Non‐nutrient...mentioning
confidence: 99%
“…For example, it has been shown in vitro that beta-lactams can suppress arachidonic acid release from platelets to form thromboxanes [74]. In another study, a combination of ampicillin and chloramphenicol increased eicosanoid concentrations [75]. Therefore, both antibiotics might have an impact on eicosanoid formation.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] Moreover, it is worth noting that CHL has been identified as a potential carcinogen with documented immunosuppressive effects upon excessive usage. [9,10] Chloramphenicol enters the gastrointestinal tract and directly or indirectly interacts with digestive enzymes. However, the interaction between CHL and digestive enzymes remains poorly understood, including its potential harmful effects on the functional activity of pepsin.…”
Section: Introductionmentioning
confidence: 99%
“…This process can potentially impede alterations in the protein's microenvironment, conformational dynamics, and overall structure, thereby influencing their biological activity and functionality [7,8] . Moreover, it is worth noting that CHL has been identified as a potential carcinogen with documented immunosuppressive effects upon excessive usage [9,10] …”
Section: Introductionmentioning
confidence: 99%